2014
DOI: 10.1002/pc.23005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanocrystalline cellulose on structure and properties of natural rubber/silica composites

Abstract: A complex of resorcinol and hexamethylenetetramine (RH) was utilized to modify nanocrystalline cellulose (NCC). The modified NCC (MNCC) was then mixed with natural rubber (NR) filled silica. The structure, processing properties, mechanical properties, and dynamic compression fatigue properties of the NR/MNCC/Silica nanocomposites were characterized by scanning electron microscopy (SEM), rubber processing analyzer, electronic tensile machine, and dynamic compression fatigue performance tester. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 38 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…So this rise was mainly attributed to the physical interaction of RH with filler. The hydrogen bond of RH/NCC has been verified in our previous publications [28]. It could be deduced that, with the existence of RH, NCC network seemed to be enhanced by hydrogen bond via RH.…”
Section: Rpa 2000 Analysis Of Nr/br/sbrmentioning
confidence: 69%
“…So this rise was mainly attributed to the physical interaction of RH with filler. The hydrogen bond of RH/NCC has been verified in our previous publications [28]. It could be deduced that, with the existence of RH, NCC network seemed to be enhanced by hydrogen bond via RH.…”
Section: Rpa 2000 Analysis Of Nr/br/sbrmentioning
confidence: 69%
“…The FT‐IR profiles of the modified membranes show an increase in the intensity of the broad peak at 3000–3500 cm −1 , which originates from the aliphatic secondary amino groups of PDDA and the OH stretching of CNC in Nafion‐[PDDA/CNC] 20. In addition, new peaks appeared at 2921 and 2850 cm −1 , corresponding to the CH 2 stretching of PDDA and CNC . The FT‐IR data clearly show that PDDA and CNC accumulate in Nafion‐[PDDA/CNC] 20 .…”
Section: Resultsmentioning
confidence: 94%
“…36,37 The FT-IR data clearly show that PDDA and CNC accumulate in Nafion-[PDDA/CNC] 20 . 36,37 The FT-IR data clearly show that PDDA and CNC accumulate in Nafion-[PDDA/CNC] 20 .…”
Section: 35mentioning
confidence: 99%
“…The results indicated that the cross-link density was related to the state of PF coating. At 100 °C, SiCB was coated uniformly with a thin layer of PF, which provided a stronger interaction through chemical bonds with NR molecular chains [30], leading to improved cross-link density. Therefore, PF can strengthen the interfacial bonding and link more closely between rubber and filler.…”
Section: Resultsmentioning
confidence: 99%